2023
DOI: 10.1042/bcj20220614
|View full text |Cite
|
Sign up to set email alerts
|

LRRC8A is responsible for exosome biogenesis and volume regulation in colon cancer cells

Abstract: Exosomes are vital mediators for intercellular communications in the tumor microenvironment to accelerate colon cancer progression. Leucine-rich repeat-containing 8A (LRRC8A), the core component of the volume-regulated anion channel, is closely associated with acquiring heterogeneity for tumor cells. However, the role of LRRC8A in the exosomes remains largely unknown. Here, we reported that LRRC8A was one of the compositions in the exosomes released from colon cancer HCT116 cells. Downregulation of LRRC8A prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Recently, it has been revealed that LRRC8A is one of the components of the exosomes released from colon cancer HCT116 cells. Exosomes play a crucial role in intercellular communications within the microscopic tumor environment, facilitating the progression of colon cancer [ 62 ]. Additionally, compromised cellular junctions might enhance metastatic potential, leading to a more aggressive and invasive tumor phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been revealed that LRRC8A is one of the components of the exosomes released from colon cancer HCT116 cells. Exosomes play a crucial role in intercellular communications within the microscopic tumor environment, facilitating the progression of colon cancer [ 62 ]. Additionally, compromised cellular junctions might enhance metastatic potential, leading to a more aggressive and invasive tumor phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, VRAC has been suggested to play a role in regulating cell growth, movement and apoptosis of tumor cells ( Fraser and Pardo, 2008 ; Arcangeli and Becchetti, 2015 ; Sirianant et al, 2016 ; Prevarskaya et al, 2018 ). Downregulation of LRRC8A subunit has been reported to suppress the growth or proliferation of different cancer cell types, including human glioblastoma cells ( Rubino et al, 2018 ), colorectal carcinoma cells ( Fujii et al, 2018 ), esophageal squamous cell carcinoma cells ( Konishi et al, 2019 ), gastric cancer ( Kurashima et al, 2021 ), colon cancer ( Zhang et al, 2018 ; Zhang et al, 2023 ) and cervical cancer ( Chen et al, 2023 ), while LRRC8A overexpression reportedly facilitated hepatocellular carcinoma cell growth ( Lu et al, 2019 ). In vivo studies in nude mouse models have also shown that LRRC8A downregulation suppressed the proliferation of colon carcinoma, hepatocellular carcinoma, and cervical cancer ( Zhang et al, 2018 ; Lu et al, 2019 ; Chen et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chloride ions are the most abundant anion and are involved in many different physiological and pathological processes. The molecular constituents of the volume-regulated anion channel (VRAC) are diverse, including LRRC8A-E, CFTR, ClCs, and more ( 3 ). The ClC-3 chloride channel, encoded by Clcn3 , is critical for several basic cellular functions, such as cell volume regulation, proliferation, apoptosis, differentiation, and β cell insulin secretion ( 4 ).…”
Section: Introductionmentioning
confidence: 99%